2010
DOI: 10.1073/pnas.1008812107
|View full text |Cite
|
Sign up to set email alerts
|

Gene-silencing reveals the functional significance of pheromone biosynthesis activating neuropeptide receptor (PBAN-R) in a male moth

Abstract: The role of pheromone biosynthesis activating neuropeptide (PBAN) in the regulation of pheromone biosynthesis of several female moth species is well elucidated, but its role in the males has been a mystery for over two decades since its discovery from both male and female central nervous systems. In previous studies we have identified the presence of the gene transcript for the PBAN-G-protein coupled receptor (PBAN-R) in Helicoverpa armigera male hair-pencil-aedaegus complexes (male complexes), a tissue struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 50 publications
5
22
0
Order By: Relevance
“…PBAN-R RNAi has already been shown to inhibit PBAN-R transcription in moths [47], [51], [52], resulting in reduced sex pheromone production, which is similar to our results for SolinPBAN-R RNAi and reduced trail pheromone production in fire ants.…”
Section: Resultssupporting
confidence: 91%
“…PBAN-R RNAi has already been shown to inhibit PBAN-R transcription in moths [47], [51], [52], resulting in reduced sex pheromone production, which is similar to our results for SolinPBAN-R RNAi and reduced trail pheromone production in fire ants.…”
Section: Resultssupporting
confidence: 91%
“…RNAi silencing techniques have proven to be of great usefulness in functional analysis of genes (Ohnishi et al ., 2006; Bober & Rafaeli, 2010). In the present study, RNAi silencing of the HeaSP‐R gene has demonstrated the involvement of this receptor in aspects of reproductive behaviour including responses to mating and to injected synthetic Drm SP.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi mediated by dsRNA ingestion requires higher dosage and multiple administrations until the onset of silencing in insects when compared to RNAi via injection in the haemolymph (Chen et al, 2008;Tian et al, 2009;Zhu et al, 2011), although dosages needed to elicit effect via injection in H. armigera remain measured in micrograms (Bober and Rafaeli, 2010;Cai et al, 2014;Du et al, 2012;Hou et al, 2012;Qiao et al, 2014;Sivakumar et al, 2007;Tang et al, 2012;Wang et al, 2010;Yang and Han, 2014a).…”
Section: Nucleotide Dsrna Concentrationmentioning
confidence: 99%